Are Human Rights Universal? - Al-Fahad , Fahad A. S (Technium Business and Management, 2024)
In this essay, I will argue that "human rights are not universal" by analyzing the human rights discourse and the narratives that control it. Challenging the claim of universality will be highlighted from three different angles. First, the essay argues that the experience of women is often overlooked in the human rights narrative; making it non-inclusive. Furthermore, the second major issue with human rights universality is that such a claim is driven by western liberal thought that has hegemonic agenda instead of universal purposes. Finally, the third dimension that I will focus on in this essay is the strong presence of neoliberal ideas in the human rights discourse which aim at serving the interests of the few elites rather than all people around the globe. Before going into the analysis, I will start by explaining a key term in this essay which is the “universality” of human rights by shedding the light on the context of the Universal Declaration of Human Rights (UDHR).